Foam cell‐derived 4‐hydroxynonenal induces endothelial cell senescence in a TXNIP‐dependent manner. Issue 8 (5th March 2015) - Riahi, Yael; Kaiser, Nurit; Cohen, Guy; Abd‐Elrahman, Ihab; Blum, Galia; Shapira, Oz M.; Koler, Tomer; Simionescu, Maya; Sima, Anca V.; Zarkovic, Neven; Zarkovic, Kamelija; Orioli, Marica; et al.
Abstract Vascular endothelial cell (VEC) senescence is considered an early event in the development of atherosclerotic lesions. Stressful stimuli, in particular oxidative stress, have been linked to premature senescence in the vasculature. Foam cells are a major source of reactive oxygen species and may play a role in the induction of VEC senescence; hence, we investigated their involvement in the induction of VEC senescence in a co‐culture transwell system. Primary bovine aortic endothelial cells, exposed to the secretome of THP‐1 monocyte‐derived foam cells, were analysed for the induction of senescence. Senescence associated β‐galactosidase activity and the expression of p16 and p21 were increased, whereas phosphorylated retinoblastoma protein was reduced. This senescent phenotype was mediated by 4‐hydroxnonenal (4‐HNE), a lipid peroxidation product secreted from foam cells; scavenging of 4‐HNE in the co‐culture medium blunted this effect. Furthermore, both foam cells and 4‐HNE increased the expression of the pro‐oxidant thioredoxin‐interacting protein (TXNIP). Molecular manipulation of TXNIP expression confirmed its involvement in foam cell‐induced senescence. Previous studies showed that peroxisome proliferator‐activated receptor (PPAR)δ was activated by 4‐hydroalkenals, such as 4‐HNE. Pharmacological interventions supported the involvement of the 4‐HNE‐PPARδ axis in the induction of TXNIP and VEC senescence. The association of TXNIP with VEC senescence was further supported by immunofluorescent staining of human carotid plaques in which the expression of both TXNIP and p21 was augmented in endothelial cells. Collectively, these findings suggest that foam cell‐released 4‐HNE activates PPARδ in VEC, leading to increased TXNIP expression and consequently to senescence.